Концепт перфектності в семантичній структурі турецького абсентив-перфекта - Сорокін, С.В. (Культура народов Причерноморья, 2003)
There has been investigated the concept of perfectivity as one of the two key components of the semantic structure of the Turkish Absentive-Perfect Tense. There has been analyzed the concepts connected with perfective semantics, peculiarities of their communicative realization. The article is a part of the integral investigation of the categories of temporality, aspectuality and modality as a functional field of the Turkish language. The main methodological positions of the research are the functional method, anthropocentric, linguo-cognitive and linguoculturological approaches.